Information Literacy Kelayakan Kompetensi Lulusan Sekolah dan Pengembangannya di Universitas Riset - Rizal Syaiful Haq (Buletin Al-Turas, 2006)
Information literacy is an academic competency for all students with their indicators in any levels of education in INdonesia from Elementary School (SD) untill University (PT). Even more in research university like UIN Syarif Hidayatullah Jakarta, in order every student to have competency in his/her major and minor.